Aspek Ontologis dalam Ilmu Pengetahuan - Nova Liza; Zurhidayati Zurhidayati; Ardimen Ardimen (Departement of Mathematics Education, 2024)
Abstract This article explains the nature of scientific ontology by highlighting its contribution to understanding existence and reality. Ontology is seen as a theoretical basis that studies the nature and existence of entities and phenomena in various scientific disciplines. The contribution of ontology in the management of Islamic education is examined, highlighting the importance of understanding human existence and its relationship with God in the context of Islamic education. In addition, this article discusses the application of ontology in developing student literacy as well as directing curriculum development and teaching methodology in Islamic education management. Thus, this article provides a comprehensive overview of the role of ontology in understanding science and its application in the context of Islamic education, and emphasizes the importance of developing and improving ontological understanding to deepen human knowledge.